Proto-Bantu Existential Locational Construction(s) - Devos, Maud; Bernander, Rasmus (My University, 2022)
This chapter proposes a Proto-Bantu reconstruction of existential constructions based on a convenience sample of 180 Bantu languages, which points towards “existential locationals” (ELs) as a suitable base for comparison. ELs include inverse-locational predications as well as expressions of generic existence. We develop a detailed typology of ELs through a careful examination of the morphosyntactic variation which their building blocks display across Bantu. This typology clearly singles out two types of ELs with high frequencies and Bantu-wide distributions, which are reconstructable to at least node 5 in the phylogenetic tree of the Bantu family of Grollemund et al. (2015). Both display locative subject markers and “figure inversion” in relation to plain locational constructions. The difference between the main types lies in the selection of the copula: either a locative or a comitative one. North-Western and Central-Western Bantu languages show few reflexes of the suggested reconstructions. Instead, they often have non-inverted ELs which are cross-linguistically uncommon or, less frequently, ELs involving expletive inversion. The non-dedicated EL can be considered a retention of the original structure or a (contact-induced) innovation. Our preference goes to the second hypothesis assuming that a severe reduction of (locative) noun classes and ensuing (locative) agreement triggered a more rigid word order and consequently non-inverted ELs or inverted expletive ELs exempt of locative marking.
Keywords: Proto-Bantu; Locational Constructions; HUMANITIES and RELIGION::Languages and linguistics::Other languages::Bantu languages